Wave energy flux variability and trend along the United Arab Emirates coastline based on a 40-year hindcast. (November 2020) - Vieira, Filipe; Cavalcante, Georgenes; Campos, Edmo; Taveira-Pinto, Francisco
Abstract: Wave climate and associated energy characterization is essential for an assessment of a country's renewable energy potential. A wave model was validated against satellite data with good performance in terms of error metrics. The hindcast data, covering the period 1979–2018, was used to describe the spatial, seasonal and interannual variability and trend of wave energy flux along the United Arab Emirates coastline. The annual mean wave energy flux along the study area is higher at the central region reducing towards the south and north. The wave energy shows a clear seasonality and interannual variability for all locations with higher and lower energy during winter and autumn, respectively. A trend analysis of the historical data indicates an increase in annual mean energy flux along the coast. Alongshore, seasonal and interannual variability of wave energy flux and direction should be considered in the initial stages of marine renewable energy projects. A detailed analysis of historical wave energy trends and influence of large-scale climate indices will be particularly relevant for longer-term projects. Highlights: Detailed characterization of wave energy along the United Arab Emirates coastline. Validated SWAN model covering a period of 40 years used to provide data for analysis. Spatial, seasonal and interannual variability of wave energy is presented. The analysis of the historical data shows clear positive trend in wave energy flux.